Development of Bio-Entrepreneurship Book: Review of Its Practicality and Effectiveness in Biological Entrepreneurship Learning - Ita, Ita; Himmah, Nurul; Destiara, Meyninda (Proceeding International Conference on Religion, Science and Education, 2026)
One of the graduate profiles of the Biology Education Study Program, as a form of preparation for the demands of the 21st century, is entrepreneurs in the field of biology. To achieve this goal, it is necessary to instill an entrepreneurial spirit in higher education biology learning, in this case in biology entrepreneurship courses. The biology entrepreneurship course itself is a new course in the Biology Education Study Program, so it still requires relevant teaching materials. The limitation of teaching materials that integrate biological concepts with entrepreneurial values is the reason for the development of the Bio-Entrepreneurship Book based on local potential. The purpose of this study is to describe the practicality and effectiveness of the developed Bio-Entrepreneurship Book in biology entrepreneurship learning. This study uses Educational Design Research (EDR) with the Plomp model. The practicality and effectiveness data were tested through Tessmer evaluation, namely at the one-to-one evaluation and field test stages, with data collection techniques using questionnaires and pre-tests and post-tests. The results of the study indicate that the developed Bio-Entrepreneurship Book is practical based on student responses and effective in supporting biological entrepreneurship learning based on learning outcomes and student motivation responses. Thus, the Bio-Entrepreneurship Book is suitable for use as an alternative teaching material that can foster students’ entrepreneurial spirit.